Physics of solid–liquid interfaces: from the Young equation to the superhydrophobicity (Review Article) - Bormashenko, Edward (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
The state-of-art in the field of physics of phenomena occurring at solid/liquid interfaces is presented. The notions of modern physics of wetting are introduced and discussed including: the contact angle hysteresis, disjoining pressure and wetting transitions. The physics of low temperature wetting phenomena is treated. The general variational approach to interfacial problems, based on the application of the transversality conditions to variational problems with free endpoints is presented. It is demonstrated that main equations, predicting contact angles, namely the Young, Wenzel and Cassie–Baxter equations arise from imposing the transversality conditions on the appropriate variational problem of wetting. Recently discovered effects such as superhydrophobicity, the rose petal effect and the molecular dynamic of capillarity are reviewed.